Surgical Dental Treatment for Military Personnel: Where and When?—A Case Report. Issue 11 (1st November 2014) - Stoetzer, Marcus; Schmidt, Roland; Gellrich, Nils-Claudius; von See, Constantin
ABSTRACT: Introduction: Oral health is essential for combat readiness. The classification for combat readiness includes the Dental Fitness Categories, which are used to estimate a soldier's need for emergency dental care while deployed overseas. When the issue at hand is in regard to unerupted or additional teeth, the treating dentist faces a difficult decision since there is no evidence-based practice guidelines. Case Report: An otherwise healthy 20 year-old soldier initially presented to his general physician (Role I) with toothache in the lower jaw. The initial referral to a general dentist (Role II) led to a diagnosis of an additional tooth 45; therefore, he was transferred to the oral surgeon (Role III). A computed tomography scan revealed fully retained besides the additional 45, wisdom teeth, and additional wisdom teeth, as well as retained tooth 23. After careful consideration, osteotomies of all retained teeth were performed under general anesthesia. A titanium miniplate was placed for stabilization. Discussion: Despite variability among dentists in assigning a particular Dental Fitness Class, the clinical and radiologic examination must take into account treatment options that may become necessary for unerupted and retained teeth.